Struktur Puisi “Perempuan-Perempuan” Karya D. Kemalawati - Yani*, Ulfi; Yanti, Diana; Solihati, Nani (Universitas Suryakanca, 2025)
This article will explain the physical structure in the poem Perempuan-perempuan by D. Kemalawati. The approach in this study uses a qualitative descriptive method. Data in the study were collected using content analysis techniques (text). The results of this study reveal that the physical structure and diction of the poem utilize connotative language that provides figurative meaning and denotative language that is simple but full of meaning, while the imagery or imagery in this poem utilizes visual and auditory imagery to strengthen the atmosphere of the poem and make it easier for readers to understand the poem. The message in the poem explains that a woman must survive amidst all limitations.Keywords: poetry; physical structure; imagery AbstrakArtikel ini akan memaparkan struktur fisik dalam puisi Perempuan-perempuan karya D. Kemalawati. Pendekatan dalam penelitian ini menggunakan metode deskriptif kualitatif. Data dalam penelitian dikumpulkan menggunakan teknik content analysis (teks). Hasil penelitian ini mengungkapkan bahwa struktur fisik dan diksi puisi memanfaatkan bahasa konotatif yang memberikan makna kiasan dan bahasa denotatif yang bersifat sederhana tapi penuh makna, sedangkan citra atau pengimajian dalam puisi ini memanfaatkan citraan visual dan auditif untuk memperkuat suasana puisi dan memudahkan pembaca dalam memahami puisi. Amanat dalam puisi menjelaskan bahwa seorang perempuan harus tetap bertahan di tengah segala keterbatasan.Katakunci: puisi; struktur fisik; citraan